Reduced Medial Prefrontal Control of Palatable Food Consumption Is Associated With Binge Eating Proneness in Female Rats - Sinclair, Elaine B.; Klump, Kelly L.; Sisk, Cheryl L. (Frontiers in Behavioral Neuroscience, 2019)
Binge eating is the core, maladaptive eating behavior that cuts across several major types of eating disorders. Binge eating is associated with a significant loss of control over palatable food (PF) intake, and deficits in behavioral control mechanisms, subserved by the prefrontal cortex (PFC), may underlie binge eating. Few studies, to date, have examined whether the PFC is directly involved in the expression of binge eating. As such, the present study investigated the functional role of the medial PFC (mPFC) to PF consumption, in an individual differences rat model of binge eating proneness. Here, we tested the hypothesis that binge eating proneness (i.e., high levels of PF consumption) is associated with reduced mPFC-mediated behavioral control over PF intake. In experiment 1, we quantified PF-induced Fos expression in both excitatory and inhibitory neurons within the mPFC of binge eating prone (BEP) and binge eating resistant (BER) female rats. In experiment 2, we pharmacologically inactivated the mPFC of BEP and BER female rats, just prior to PF exposure, and subsequently quantified PF intake and scores of feeding behavior. While most Fos-expressing neurons in the mPFC of both BEPs and BERs were of the excitatory phenotype, fewer excitatory neurons were engaged by PF in BEPs than in BERs. Moreover, pharmacological inactivation of the mPFC led to a significant increase in PF intake in both BEPs and BERs, but the rise in PF consumption was stronger in BEPs than in BERs. Thus, these data suggest that lower, PF-induced excitatory tone in the mPFC of BEP rats may lead to a weaker, mPFC-mediated behavioral “brake” over excessive PF intake.